A COMPARATIVE STUDY OF LITERARY MOVEMENTS IN 20TH CENTURY EUROPE - Qosimova Saida Umidjon qizi; Abduramanova Diana Valerivna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article represents a comparative study of the four major literary movements which dominated European literature in the 20th century. Namely, these were Modernism, Surrealism, Existentialism, and Postmodernism. Each movement originated in response to various historical and cultural changes and intellectual transformations of its time. They offered unique ways of approaching art and literature. Modernism rebelled against traditional forms for fragmentation and subjectivity. While surrealism tried to unleash the unconscious mind, Existentialism fought to find meaning in a world full of absurdity. On the other side, postmodernism did deconstruct grand narratives into irony, metafiction, and playfulness. Through these comparative analyses, the article discusses how such movements reflect the variable literary concerns of 20th-century Europe and how they go on to influence contemporary thought.